Current Trends in Regional Anaesthesia for Paediatric Surgery: Focus on Trunk Blocks and Axillary Block for Upper Limb Surgery with Minimal Sedation – A Systematic Review - Khan, Muhammad Hassan; Hussain, Mehdi; Walayat, Farhan; Aljazarah, Khamees Kamal; Chaudhry, Muhammad Raheel (Journal of Neonatal Surgery, 2025)
Background: Regional anesthesia in pediatrics, particularly trunk blocks, and axillary blocks is increasingly recognized for its efficacy in managing pain during surgery. These techniques are gaining traction due to their ability to reduce reliance on general anesthesia and minimize postoperative pain. However, there are ongoing challenges in their implementation, including patient safety concerns, technical complexities, and workforce adaptation. Despite these challenges, regional anesthesia holds significant promise for improving outcomes in pediatric surgeries, especially in conjunction with minimal sedation. Objective: This study aims to evaluate the current trends and practices in regional anesthesia for pediatric surgery, focusing on the use of trunk blocks and axillary blocks for upper limb surgeries with minimal sedation. It explores the advantages, challenges, and future directions for the widespread adoption of these techniques in pediatric care, with a particular emphasis on their impact on pain management, safety, and overall surgical outcomes. Method: A systematic review of the literature was conducted, adhering to the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines. The search included studies published in the last five years (2019-present), sourced from databases such as PubMed, Scopus, and ScienceDirect. Additionally, a structured survey was administered to 190 healthcare professionals, including anaesthesiologists, pediatric surgeons, and nurses, to gather insights on current practices, advantages, and challenges related to regional anesthesia in pediatrics. Data were analyzed to identify key trends, strengths, weaknesses, and areas requiring further research. Results: The review found that trunk blocks (60%) and axillary blocks (55%) are the most commonly used regional anesthesia techniques in pediatric surgeries. The primary benefits cited by healthcare professionals included reduced postoperative pain (65%), faster recovery times (55%), and a lower risk of complications (45%). However, concerns about the technical complexity of these procedures (40%), data privacy (35%), and workforce adaptation (30%) were also highlighted. The combination of minimal sedation with regional anesthesia was considered effective by 50% of respondents, particularly for upper limb surgeries. Conclusion: Regional anesthesia, specifically trunk and axillary blocks, is poised to play a significant role in pediatric surgery by offering enhanced pain management and improved recovery times. While the adoption of these techniques offers numerous advantages, addressing challenges such as technical training, patient safety, and workforce adaptation is essential for their successful implementation. Future research should focus on refining these anesthesia techniques, improving training for healthcare professionals, and exploring regulatory frameworks to support their integration into pediatric practice